2015
DOI: 10.1002/pat.3615
|View full text |Cite
|
Sign up to set email alerts
|

Chiral, pH responsive hydrogels constructed by N -Acryloyl-alanine and PEGDA/α -CD inclusion complex: preparation and chiral release ability

Abstract: Chiral, pH-responsive hydrogels are constructed by poly(ethylene glycol) diacrylate/α-cyclodextrin (PEGDA/α-CD) inclusion complex and L-N-acryloyl-alanine or D-N-acryloyl-alanine (L-NAA or D-NAA) by an effective free radical polymerization approach. PEGDA containing two C=C end groups was used simultaneously to introduce α-CD units in the resulting hydrogels and to serve as a cross-linking agent, by which forming the designed hydrogels in quantitative yield. Hydrophilic α-CD moieties acted as pore-forming agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…In a later study, Wu found that chiral hydrogels derived from D-or L-N-acryloyl-alanine (NAA) and inclusion complexes between poly(ethylene glycol) diacrylate (PEGDA) and α-CD could show different rates of adsorption and release for both enantiomers of trans-4hydroxyproline (HP). 251 The hydrogel containing L-NAA preferentially adsorbed D-HP, indicated stronger enantioselective interactions between them. On the other hand, the D-NAA-containing hydrogel showed greater uptake of the opposite guest enantiomer.…”
Section: T H I S C O N T E N T Imentioning
confidence: 96%
See 1 more Smart Citation
“…In a later study, Wu found that chiral hydrogels derived from D-or L-N-acryloyl-alanine (NAA) and inclusion complexes between poly(ethylene glycol) diacrylate (PEGDA) and α-CD could show different rates of adsorption and release for both enantiomers of trans-4hydroxyproline (HP). 251 The hydrogel containing L-NAA preferentially adsorbed D-HP, indicated stronger enantioselective interactions between them. On the other hand, the D-NAA-containing hydrogel showed greater uptake of the opposite guest enantiomer.…”
Section: T H I S C O N T E N T Imentioning
confidence: 96%
“…When a racemic hydrogel comprising equal quantities of ( R )- and ( S )-polymers was used for enantio­selective guest release, d - and l -mandelic acid were released at the same rate. In a later study, Wu found that chiral hydrogels derived from d - or l - N -acryloyl-alanine (NAA) and inclusion complexes between poly­(ethylene glycol) diacrylate (PEGDA) and α-CD could show different rates of adsorption and release for both enantiomers of trans -4-hydroxyproline (HP) . The hydrogel containing l -NAA preferentially adsorbed d -HP, indicated stronger enantioselective interactions between them.…”
Section: Hydrogel Molecular Sensors and Biosensorsmentioning
confidence: 99%
“…As an emergency field, actuators composed of responsive materials, which convert external stimuli to mechanical deformation or movement, [1] have gained increased interest in the fields of soft robot, [2] drug delivery vehicles, [3,4] tissue engineering, and biological machines. [5][6][7] According to the external stimuli, actuators are divided into hydraulic, [8] pneumatic, [9] electrical, [10] magnetic, [11] light-driven [12] actuators, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally occurring and synthetic, chiral polymers are commercially used as column chromatography packing materials or membranes for chiral resolution of organic racemic mixtures . These polymers can be obtained through the optically functionalization of a polymer or polymerization of an optically active monomer, which leads to higher functionalization and purity. Hydrogels are lightly crosslinked hydrophilic polymer networks with the ability to absorb and retain a large amount of water .…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels are lightly crosslinked hydrophilic polymer networks with the ability to absorb and retain a large amount of water . Chiral hydrogels have aroused increasing attention in chirality‐responsive polymers and enantio‐differentiating adsorption/release …”
Section: Introductionmentioning
confidence: 99%